1998
DOI: 10.1161/01.res.82.6.722
|View full text |Cite
|
Sign up to set email alerts
|

Response of Intra-acinar Pulmonary Microvessels to Hypoxia, Hypercapnic Acidosis, and Isocapnic Acidosis

Abstract: To elucidate the differential reactivity of pulmonary microvessels in the acini to hypoxia, excessive CO2, and increased H+, we investigated changes in the diameter of precapillary arterioles, postcapillary venules, and capillaries in isolated rat lungs on exposure to normocapnic hypoxia (2% O2), normoxic hypercapnia (15% CO2), and isocapnic acidosis (0.01 mol/L HCl). Microvascular diameters were precisely examined using a real-time confocal laser scanning luminescence microscope coupled to a high-sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 31 publications
3
30
1
Order By: Relevance
“…In another study, it was found that this hypercapnia-associated venule dilatation in intact lungs is significantly attenuated in hyperoxia-injured lungs due to inhibition of COX activity by excessive NO [7]. However, these previous studies did not determine the relative contributions of COX (COX-1 and COX-2) and nitric oxide synthase (NOS) isoforms (endothelial constitutive (ecNOS) and inducible NOS (iNOS)) to the abnormal acinar microvessel response to HA [4,7]. Furthermore, they did not partition the abnormal microvessel response to HA into that caused by a high carbon dioxide concentration and that by a high hydrogen ion concentration, both of which occur under conditions of HA.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In another study, it was found that this hypercapnia-associated venule dilatation in intact lungs is significantly attenuated in hyperoxia-injured lungs due to inhibition of COX activity by excessive NO [7]. However, these previous studies did not determine the relative contributions of COX (COX-1 and COX-2) and nitric oxide synthase (NOS) isoforms (endothelial constitutive (ecNOS) and inducible NOS (iNOS)) to the abnormal acinar microvessel response to HA [4,7]. Furthermore, they did not partition the abnormal microvessel response to HA into that caused by a high carbon dioxide concentration and that by a high hydrogen ion concentration, both of which occur under conditions of HA.…”
mentioning
confidence: 98%
“…The vascular reactivity of pulmonary microvessels, especially acinar microvessels, in response to acidosis induced by either alveolar hypercapnia (hypercapnic acidosis (HA)) or metabolic disturbance (isocapnic acidosis (IA)) is one of the major modulators regulating the distribution of pulmonary blood flow [1][2][3][4]. An exact knowledge of acinar microvessel behaviour in acidosis is absolutely necessary when treating patients with diseased lungs using controlled ventilation with permissive hypercapnia, which has increasingly assumed an important place in managing acute lung injury [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data on the extent of HPV matches well to results obtained with a different experimental approach. Yamaguchi et al have applied isolated rat lungs to examine microvessels with diameter of 20-30 µm by real-time confocal laser scanning luminescence microscopy coupled to a high-sensitivity camera with an image intensifier 10 . They observed a mean reduction in diameter of 2.7 µm after exposure of the lungs to hypoxia.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The intra-acinar artery feeding an individual pulmonary acinus with blood represents a partially muscular segment 6 . Likewise, the pulmonary arterial system does not represent a uniform structure regarding the hypoxic response but exhibits marked regional diversity 9,10 . For instance, in proximal pulmonary arteries isolated from rat lungs hypoxia induces a biphasic response, displaying an initial rapid contraction of short duration which -after incomplete relaxation -is followed by a second slow but sustained contraction 11 .…”
Section: Introductionmentioning
confidence: 99%